EFEK SITOTOKSISITAS SENYAWA BIOAKTIF TUMBUHAN TERHADAP SEL KANKER PAYUDARA -SKBR3 CELL LINE : A SYSTEMATIC REVIEW - Rita Maliza; Azizah Amatu zikrah; Chairunnisa Azzahra Azzahra H; Hylda; Aprilia Cassa Nova (Jurnal Insan Farmasi Indonesia, 2023)
SKBR3 cancer cells are cell cultures isolated from pleural effusion of a 43-year-old Caucasian woman with metastatic breast cancer. Many plant species are used in alternative medicine which has increased in recent decades for purposes related to breast cancer. The purpose of this systematic review is to make it easier to study the potential of bioactive compounds of medicinal plants and to analyze the effects of medicinal plants on cancer cells. This study uses a search strategy to retrieve articles, including the following items: related scientific questions, database to be used, selection of keywords, inclusion and exclusion criteria, definition of results and conclusions regarding the selected articles. Eight articles that met the inclusion criteria and had compounds derived from plants were tested in vitro on the SKBR3 cell line to see their toxicity. These plant bioactive compounds play an important role in the proliferative phase, cell cycle, fatty acid synthesis and apoptosis of cancer cells.